PERAN MADRASAH DALAM MEMBANGUN MODERASI AGAMA DI INDONESIA DI ERA MILINEAL - Prihatin, Basuki (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2020)
Abstract: This study aims to describe the pattern of the spread of radicalism in madrasa by using descriptive-qualitative research. The data used include two things, namely primary data and secondary data. Data collection techniques such as documentation, interviews, observations. The results of this study indicate that radicalism enters madrasas through (1) classroom learning activities by teachers, (2) through textbooks that are suspected to contain intolerance content and (3) weak principal / foundation policies in preventing the influence of radicalism. Whereas the strategy offered is to make (1) the Teacher as a Role Mode to inculcate religious tolerance and moderation for students and have a good national outlook. (2) Critical Learning. Learning practices that are interesting, creative, critical thinking and student-centered. Teachers must be able to design learning that inspires students' reasoning; critical learning (critical thinking & critical pedagogy) and problem based learning. (3) Teacher Development, the Ministry of Religion has compiled modules that will be intended for the guidance of teachers and education personnel in the madrasa environment. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan pola penyebaran paham radikalisme di madrasah dengan menggunakan penelitian deskriptif-kualitatif. Data yang digunakan meliputi dua hal, yakni data primer dan data sekunder. Teknik pengumpulan data berupa dokumentasi, wawancara, observasi. Hasil penelitian ini menunjukkan bahwa radikalisme masuk ke madrasah adalah melalui (1) aktivitas pembelajaran di kelas oleh guru, (2) melalui buku pelajaran yang diduga memuat konten intoleransi dan (3) lemahnya kebijakan kepala sekolah/yayasan dalam mencegah masuknya pengaruh radikalisme. Sedangkan strategi yang ditawarkan adalah menjadikan (1) Guru sebagai Role Mode penanaman sikap toleransi dan moderasi beragama bagi anak didik serta berwawasan kebangsaan dengan baik. (2) Pembelajaran Kritis. Praktik pembelajaran yang menarik, kreatif, berpikir kritis dan berpusat pada siswa. Guru harus mampu mendisain pembelajaran yang menggugah nalar siswa; pembelajaran kritis (critical thinking & critical pedagogy) dan problem based learning. (3) Pembinaan Guru, Kementrian Agama telah menyusun modul yang akan diperuntukkan bagi pembinaan guru dan tenaga pendidikan di lingkungan madrasah.